Noncanonical necrosis in 2 different cell types in a Caenorhabditis elegans NAD+ salvage pathway mutant. Issue 4 (10th February 2022) - Reza, Rifath N; Serra, Nicholas D; Detwiler, Ariana C; Hanna-Rose, Wendy; Crook, Matt
Abstract: Necrosis was once described as a chaotic unregulated response to cellular insult. We now know that necrosis is controlled by multiple pathways in response to many different cellular conditions. In our pnc-1 NAD + salvage deficient Caenorhabditis elegans model excess nicotinamide induces excitotoxic death in uterine-vulval uv1 cells and OLQ mechanosensory neurons. We sought to characterize necrosis in our pnc-1 model in the context of well-characterized necrosis, apoptosis, and autophagy pathways in C. elegans . We confirmed that calpain and aspartic proteases were required for uv1 necrosis, but changes in intracellular calcium levels and autophagy were not, suggesting that uv1 necrosis occurs by a pathway that diverges from mec-4d -induced touch cell necrosis downstream of effector aspartic proteases. OLQ necrosis does not require changes in intracellular calcium, the function of calpain or aspartic proteases, or autophagy. Instead, OLQ survival requires the function of calreticulin and calnexin, pro-apoptotic ced-4 (Apaf1), and genes involved in both autophagy and axon guidance. In addition, the partially OLQ-dependent gentle nose touch response decreased significantly in pnc-1 animals on poor quality food, further suggesting that uv1 and OLQ necrosis differ downstream of their common trigger. Together these results show that, although phenotypically very similar, uv1, OLQ, and touch cell necrosis are very different at the molecular level.